The Horizontal Alignment Design Jalan Prabumulih-Simpang Belimbing Muara Enim, South Sumatra - Anisa Hanayya Pratiwi; Andri Irfan Rifa'i (LEADER: Civil Engineering and Architecture Journal, 2023)
Road geometric planning is part of road planning, whose main objective is horizontal alignment and vertical alignment to fulfill the road function, namely to provide maximum comfort for traffic flow according to the planned speed. To satisfy the road infrastructure, we need to have geometric planning of the road, which is part of the road planning that focuses on planning physical form. In this paper, we will discuss the alignment horizontal of the road so that it can be well-planned. The location of the horizontal alignment design is in Jalan Prabumulih-Simpang Belimbing-Muara Enim, South Sumatra, starting from STA 80+000 to STA 82+050. This paper uses road class regulation based on road functions and classifications, which refer to Indonesia’s 2021 Road Design Standard. Based on the horizontal alignment geometric design results for Jalan Prabumulih-Simpang Belimbing-Muara Enim at STA 80+000 to STA 82+050, it could conclude that Jalan Prabumulih-Simpang Belimbing-Muara Enim at STA 80+000 to STA 82+050 is a category class IIC collector road with design parameters of design speed (VR) 80 km/hour and max slope (e) 8%. Based on the calculations, the dimensional radius (R) is 358 m, with the intersection angle (α) is 45°. The horizontal curved length (Lc) is 211,03 m. In this paper, the authors used the Spiral - Circle – Spiral (SCS) type, which is safe for drivers according to the condition. This calculation uses the Road Class Regulation based on road functions and classification, which refer to Indonesia’s 2021 Road Design Standard.